An Exploration of Code Switching Used by English Teachers at SMP N 7 Medan - Pandiangan, Kevin Valentino; Tarigan, Natalia Widya Pasca; Wariyati, Wariyati (ELT (English Language Teaching Prima Journal), 2025)
This qualitative study looks at how English teachers use code switching in the classroom, focusing on its types, functions, and how it affects teaching in an Indonesian EFL setting. The study took place at a junior high school in Medan and included classroom observations and semi-structured interviews with a small number of English teachers. The results showed that code switching is Often used as a strategic teaching tool to help students understand better, control classroom interactions, and give emotional support. Teachers often switched codes between sentences and within sentences, mostly going from English to Bahasa Indonesia. The study found that code switching has a number of teaching uses, such as helping students understand concepts, translating vocabulary, and keeping students interested. Teachers thought code switching was a good thing because it helped people with different languages talk to each other in a meaningful way. But there were worries that people might rely too much on their first language, which could make it harder for them to learn English. The study's conclusion is that code switching can help teachers do their jobs well in EFL classrooms if they use it wisely. It suggests that teachers come up with clear plans for using code switching and that more research be done on how students feel about it and how it affects their learning.